DETERMINAN AKUNTABILITAS PENGELOLAAN DANA DESA DENGAN ASA TRI PANTANGAN SEBAGAI VARIABEL MODERASI - Sri Ayem; Suyanto Suyanto; Yhoga Heru Pratama; Rita Oktaviani (Faculty of Economics and Business, Universitas Warmadewa, 2024)
This study aims to determine the effect of accounting understanding, understanding of laws and village internal control systems on the accountability of managing village funds with the principle of three taboos as a moderating variable. This study used a quantitative descriptive method and primary data using a questionnaire which was distributed directly to the respondents. The number of samples in this study were 94 samples from 12 village offices in Salam District, Magelang Regency. Sampling used a purposive sampling technique, namely a sampling technique based on certain target considerations. This study found that accounting understanding had no effect on accountability, while understanding laws and internal control systems had a positive effect on village fund management accountability. The principle Asas Tri Pantangan cannot moderate accounting understanding, understanding of laws and control systems for accountability in managing village funds.